Auditory evaluation in patients with type 1 diabetes - Pessin, Adriana Bueno Benito [UNESP]; Martins, Regina Helena Garcia [UNESP]; Pimenta, Walkyíria De Paula [UNESP]; Simões, Antônio Caetano Pereira [UNESP]; Marsiglia, Alessandra [UNESP]; Amaral, Amanda Vieira [UNESP] (SAGE Publications, 2008)
Objectives: We performed a prospective clinical study of the cochleovestibular symptoms and the risk cofactors and characteristics of hearing loss in patients with type 1 diabetes. Methods: Group 1 consisted of 40 patients with type 1 diabetes, and group 2 consisted of 20 control subjects without diabetes. All participants answered a questionnaire, and their medical records were reviewed. They also were submitted to otorhinolaryngological examinations and to auditory tests (pure tone audiometry and acoustic immitance and auditory brain stem response [ABR] tests). Results: Dyslipidemia, hypertension, retinopathy, and diabetic neuropathy were not frequent in the patients of group 1, but incipient nephropathy was present in 47.5% of them. The most frequent cochleovestibular symptoms were tinnitus and hearing loss. Sensorineural hearing loss was found in 4 patients of group 1 and was predominantly bilateral, symmetric, and affecting the high frequencies, coexisting with normal vocal discrimination. These patients had a longer time from diabetes diagnosis and had poor glycemia control. A delay of ABR interpeak latency I-III was observed in 11.25% of the group 1 ears. All patients of group 2 presented normal audiograms and ABR tests. Conclusions: In group 1, the most frequent cochleovestibular symptoms were tinnitus and hearing loss. The sensorineural hearing loss was mild, symmetric, and predominantly high-frequency. A delay of ABR interpeak latencies was detected in the patients of group 1 who had normal audiometric thresholds. © 2008 Annals Publishing Company. All rights reserved.
Keywords: Audiometry; Auditory brain stem response; Hearing loss; Type 1 diabetes